Vasopressin directly closes ATP-sensitive potassium channels evoking membrane depolarization and an increase in the free intracellular Ca2+ concentration in insulin-secreting cells. - Martin, S C (1989)
The effects of arginine-vasopressin (AVP) (0.01-1 microM) on membrane potential, [Ca2+]i and ATP-sensitive potassium channels have been studied in the insulin-secreting cell line RINm5F. In whole cells, with an average spontaneous cellular transmembrane potential of -64 +/- 3 mV (n = 33) and an average basal [Ca2+]i of 102 +/- 6 nM (n = 40), AVP evoked: (i) membrane depolarization, (ii) voltage-dependent Ca2+ spike-potentials and (iii) a sharp rise in [Ca2+]i. Single-channel current events recorded from excised outside-out membrane patches show that AVP closes potassium channels that are also closed by tolbutamide (100 microM) and opened by diazoxide (100 microM). AVP acts on KATP channels specifically from the outside of the membrane and a soluble cytosolic messenger appears not to be involved, since there is no channel activation in cell-attached membrane patches when the peptide is added to the bath solution.